Strategic Decision-Making with Information and Extraction Externalities: A Structural Model of the MultiStage Investment Timing Game in Offshore Petroleum Production - Lin, C.-Y. Cynthia (The Review of Economics and Statistics, 2013)
Abstract When individual petroleum-producing firms make their exploration and development investment timing decisions, positive information externalities and negative extraction externalities may lead them to interact strategically with their neighbors. This paper examines whether these inefficient strategic interactions take place by estimating a structural econometric model of the firms' multi-stage investment timing game. Results show that firms interact strategically on small tracts but not on large tracts. For small tracts, having a neighboring tract explored reduces real profits by about $26 million, while having a neighboring tract developed raises real profits by about $3.5 million.